1998
DOI: 10.1021/ma980140h
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Mechanical Performance of Polystyrene/Polyethylene Composites Prepared in Supercritical Carbon Dioxide

Abstract: Polystyrene/polyethylene composites have been prepared by the heterogeneous radical polymerization of styrene within supercritical carbon dioxide−swollen high density polyethylene (HDPE) substrates. Composition of the composites can be controlled with reaction time and initial ratio of styrene to HDPE. The polystyrene produced within the substrate is of high molecular weight. Differential scanning calorimetry and wide-angle X-ray diffraction indicate that the crystalline portion of the HDPE substrate is unaffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 33 publications
3
85
0
1
Order By: Relevance
“…This aspect is particularly important for blends where one or more component degrades or reacts to generate by-products at elevated temperatures. CO 2 -assisted impregnation and polymerization yields improved functionality relative to the homopolymer substrate and better performance as compared to conventional meltprepared polymer blends (e.g., higher modulus, [202][203][204][205] higher tensile strength, [202][203][204]206] improved impact strength, [205][206][207] increased conductivity, [208,209] and enhanced thermal stability). [209] This method also provides an avenue to blends of hydrophobic polymers (e.g., PVC or PMMA) with water-soluble polymers (such as poly(methacrylic acid) (PMAA)) that are not easily accessible by conventional means.…”
Section: Impregnation Polymerizationsmentioning
confidence: 99%
See 3 more Smart Citations
“…This aspect is particularly important for blends where one or more component degrades or reacts to generate by-products at elevated temperatures. CO 2 -assisted impregnation and polymerization yields improved functionality relative to the homopolymer substrate and better performance as compared to conventional meltprepared polymer blends (e.g., higher modulus, [202][203][204][205] higher tensile strength, [202][203][204]206] improved impact strength, [205][206][207] increased conductivity, [208,209] and enhanced thermal stability). [209] This method also provides an avenue to blends of hydrophobic polymers (e.g., PVC or PMMA) with water-soluble polymers (such as poly(methacrylic acid) (PMAA)) that are not easily accessible by conventional means.…”
Section: Impregnation Polymerizationsmentioning
confidence: 99%
“…[203,207,[211][212][213] A decisive consideration here is that the blend composition is not limited by the solubility of the monomer in the fluid or matrix phase, since polymerization depletes the monomer reservoir and permits more than the equilibrium concentration of the monomer to penetrate into the polymer substrate. [201,202,207,214,215] The resulting blends can be further modified through additional chemical means such as chemical crosslinking and surface sulfonation; [201] alternatively, the polymerization can be restricted to the substrate surface, thereby yielding a grafted surface layer. [212,216] This approach has also been implemented [212,216,217] to graft secondary species onto existing polymers.…”
Section: Impregnation Polymerizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 In addition, a significant amount of work has emerged elucidating the use of SC CO 2 as a unique solvent for polymer chemistry. 10 McCarthy et al 11 have shown that monomer can be diffused into the amorphous regions of swollen host polymer and polymerized in situ. By this process they have made some very interesting kinetically trapped polymer blends.…”
Section: Introductionmentioning
confidence: 99%